Breaksite batch mapping, a rapid method for assay and identification of DNA breaksites in mammalian cells - Kong, Qingzhong (Oxford University Press, 2001)
DNA breaks occur during many processes in mammalian cells, including recombination, repair, mutagenesis and apoptosis. Here we report a simple and rapid method for assaying DNA breaks and identifying DNA breaksites. Breaksites are first tagged and amplified by ligation-mediated PCR (LM-PCR), using nested PCR primers to increase the specificity and sensitivity of amplification. Breaksites are then mapped by batch sequencing LM-PCR products. This allows easy identification of multiple breaksites per reaction without tedious fractionation of PCR products by gel electrophoresis or cloning. Breaksite batch mapping requires little starting material and can be used to identify either single- or double-strand breaks.